The Role of Innovation for the Economic Growth and Development of the States. The Case of the Emerging Countries - Laura Diaconu (European Regional Science Association (ERSA), 2011)
At the beginning of the XXIst century, the importance of innovation is brought in light mainly due to the huge differences that exist between the living standard of the richest and of the poorest nations, differences that could be partly explained through the fact that the most advanced countries pay a greater attention to the intensive side of economic activity. The purpose of this paper is to determine the way in which innovation actually influences the economic growth and the prosperity of a country. Being known that between the stock of human and social capital, on one side, and the innovation, on the other side, there is a strong positive correlation, we will try to identify the possibilities that developing economies have to foster the innovation. The relationship between human capital and innovation will be analyzed in order to see how it could be optimized so that to obtain the best results on both micro and macroeconomic level. The example of China, whose fast development astonished the world, will serve as a model in reaching out our purposes.
Keywords: 330